An Unconventional Solution for Persistent Lateral Hip Prosthetic Friction Syndrome (LHPFS) after Revision Total Hip Arthroplasty - Matthias Wittauer; Karl Stoffel (Case Reports in Orthopedics)
We report on a 77-year-old male patient, who presented with excessive bone loss at the area of the greater trochanter after several hip revision surgeries resulting in a persistent friction syndrome caused directly by the rough surface and sharp edges of the prosthetic shoulder of a well-fixed Wagner-type revision stem. Surgery was performed by creating a cemented neotrochanter with an attached polyester patch around the proximal lateral shaft and performing a Z-plasty of the iliotibial tract. Twelve months postoperatively, the patient reported a reduction in subjective pain of 50% and improvement of the Harris Hip Score from 45 to 75 points. Without a definition in the current literature, the authors propose the term “lateral hip prosthetic friction syndrome” (LHPFS) to describe this medical condition.